2006
DOI: 10.1007/s10750-005-1613-3
|View full text |Cite
|
Sign up to set email alerts
|

Using Diatom Assemblages to Assess Urban Stream Conditions

Abstract: We characterized changes in diatom assemblages along an urban-to-rural gradient to assess impacts of urbanization on stream conditions. Diatoms, water chemistry, and physical variables of riffles at 19 urban and 28 rural stream sites were sampled and assessed during the summer base flow period. Near stream land use was characterized using GIS. In addition, one urban and one rural site were sampled monthly throughout a year to assess temporal variation of diatom assemblages between the urban and rural stream si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 25 publications
3
11
2
2
Order By: Relevance
“…The water quality factors that had strong driving effects towards the development of both phytoplankton and zooplankton communities was pH, which is consistent with the conclusions obtained in plankton‐based studies by Reynolds (2006) and Pinilla (2006). Phytoplankton communities are affected by WT to a greater extent, as phytoplankton growth and reproduction requires higher WT (Alam et al, 2001; Descy et al, 2016; Hu et al, 2018), whereas zooplankton communities are affected by Cond to a greater extent, which is consistent with the conclusions of the study on zooplankton by Walker and Pan (2006). The main chemical factors of water quality driving the development of phytoplankton communities were BOD, as appropriate levels of BOD can promote rapid phytoplankton reproduction (Hou, Song, Liu, Xiao, & Liu, 2004; Salomoni, Rocha, Callegaro, & Lobo, 2006; Zhu, Wang, Chen, Shen, & Deng, 2018).…”
Section: Resultssupporting
confidence: 78%
“…The water quality factors that had strong driving effects towards the development of both phytoplankton and zooplankton communities was pH, which is consistent with the conclusions obtained in plankton‐based studies by Reynolds (2006) and Pinilla (2006). Phytoplankton communities are affected by WT to a greater extent, as phytoplankton growth and reproduction requires higher WT (Alam et al, 2001; Descy et al, 2016; Hu et al, 2018), whereas zooplankton communities are affected by Cond to a greater extent, which is consistent with the conclusions of the study on zooplankton by Walker and Pan (2006). The main chemical factors of water quality driving the development of phytoplankton communities were BOD, as appropriate levels of BOD can promote rapid phytoplankton reproduction (Hou, Song, Liu, Xiao, & Liu, 2004; Salomoni, Rocha, Callegaro, & Lobo, 2006; Zhu, Wang, Chen, Shen, & Deng, 2018).…”
Section: Resultssupporting
confidence: 78%
“…Specific conductance often is used as a broad measure of anthropogenic influence, but is also affected by dilution (and watershed size), as well as natural factors such as soil and geology. Specific conductance has been shown to correlate well with algal assemblages in other studies in Oregon (Walker and Pan, 2006), other EUSE study areas (Potapova and others, 2005), and in Australia (Newall and Walsh, 2005). Correlations between specific conductance and anthropogenic influences can be stronger than nitrogen and phosphorus concentrations in streams with significant algal growths because of the nutrient uptake effect, which can lower nutrient levels substantially during periods of active growth.…”
Section: Multivariate Analysis Of Diatom Assemblagesmentioning
confidence: 54%
“…Sonneman et al (2001) found that diatom assemblages better reflected water-quality conditions than watershed disturbance. Walker and Pan (2006) noted that diatom assemblages captured a rural-urban landuse gradient, but the gradient also was associated with changes in water quality.…”
Section: ]mentioning
confidence: 99%
“…At local scales, urbanization has been linked to changes in stream habitat (Chin 2006, Roy et al 2003, water chemistry (Mahler et al 2005, Gilliom et al 2006, and hydrology (Poff et al 2006, USEPA 1997. Altered physical and chemical characteristics of urban streams, in turn, can serve as stressors that affect benthic algae (Coles et al 2004, Walker andPan 2006), fish (Meador et al 2005, Roy et al 2007, and macroinvertebrates (Roy et al 2003.…”
mentioning
confidence: 99%